2003
DOI: 10.1167/3.5.5
|View full text |Cite
|
Sign up to set email alerts
|

The pattern of visual deficits in amblyopia

Abstract: Amblyopia is usually defined as a deficit in optotype (Snellen) acuity with no detectable organic cause. We asked whether this visual abnormality is completely characterized by the deficit in optotype acuity, or whether it has distinct forms that are determined by the conditions associated with the acuity loss, such as strabismus or anisometropia. To decide this issue, we measured optotype acuity, Vernier acuity, grating acuity, contrast sensitivity, and binocular function in 427 adults with amblyopia or with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
438
8
8

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 454 publications
(485 citation statements)
references
References 59 publications
31
438
8
8
Order By: Relevance
“…tions (P Ͼ 0.05), and each factor significant at P Ͻ 0.02; ANOVA between amblyopic eyes and dominant eyes in amblyopic observers gives P ϭ 0.02 for interaction eye task with no other significant interactions (P Ͼ 0.05), and each factor significant at P Ͻ 0.03]. Interestingly, JS was our only amblyopic observer with residual stereovision, and previous studies have reported that amblyopes with residual stereo-competence often show transfer of the deficit in their amblyopic eye to the dominant eye (Ho et al 2005;McKee et al 2003). Our results are consistent with these previous reports in that JS is the only subject that shows conjunction impairment in both eyes.…”
Section: Observers With Abnormal Early Visual Development (Amblyopia)mentioning
confidence: 68%
See 1 more Smart Citation
“…tions (P Ͼ 0.05), and each factor significant at P Ͻ 0.02; ANOVA between amblyopic eyes and dominant eyes in amblyopic observers gives P ϭ 0.02 for interaction eye task with no other significant interactions (P Ͼ 0.05), and each factor significant at P Ͻ 0.03]. Interestingly, JS was our only amblyopic observer with residual stereovision, and previous studies have reported that amblyopes with residual stereo-competence often show transfer of the deficit in their amblyopic eye to the dominant eye (Ho et al 2005;McKee et al 2003). Our results are consistent with these previous reports in that JS is the only subject that shows conjunction impairment in both eyes.…”
Section: Observers With Abnormal Early Visual Development (Amblyopia)mentioning
confidence: 68%
“…The earliest physiological effects of amblyopia are seen in V1 (Kiorpes and McKee 1999;McKee et al 2003), and they generally occur before foveal specialization in the retina is complete at ϳ4 yr of age (Youdelis and Hendrickson 1986). Interestingly, the peripheral retina appears to develop much more rapidly than the fovea.…”
Section: Relations To Cortical Developmentmentioning
confidence: 99%
“…59 The observation that anisometropic amblyopia is associated primarily with loss of high spatial frequency contrast sensitivity, with resultant defects in steroacuity and summation, has also been demonstrated by other investigators. 56,60,61 The high spatial frequency contrast sensitivity defects in anisometropic amblyopes are important clinically. Friendly and colleagues 62 tested the visual acuity of 32 orthotropic anisometropic amblyopic children using Teller visual acuity tests and compared them to the results of acuity testing using Bailey-Lovie-Ferris charts.…”
Section: Characteristics Of Anisometropic Amblyopia Psychophysical Tementioning
confidence: 99%
“…dense unilateral cataract results in severe loss), and to the age at which the amblyogenic factor occurred. Precisely how these factors interact is as yet unknown, but it is evident that different early visual experiences result in different functional losses in amblyopia (Mckee et al 2003), and a significant factor that distinguishes performance among amblyopes is the presence or absence of binocular function.…”
Section: Introductionmentioning
confidence: 99%